Efeito da Temperatura Ambiente e da Restrição Alimentar sobre o Desempenho e a Composição de Fibras Musculares Esqueléticas de Frangos de Corte - Sartori, José Roberto [UNESP]; Gonzales, Elisabeth [UNESP]; Pai, Vitalino Dal [UNESP]; De Oliveira, Henrique Nunes [UNESP]; Macari, Marcos [UNESP] (My University, 2001)
This experiment aimed to evaluate the effects of environmental temperature and feed restriction on performance and characteristics of fiber types in the flexor hallucis longus muscle of male broilers. Three hundred twenty four five-day-old male chicks were allotted to a split plot design, where the main treatments were three feeding programs (ad libitum, early restriction - 8-14 days; later restriction - 29-35 days) and three environmental temperatures of growth (heat, termoneutral and cold) in a completely randomized factorial 3 × 3 schedule. The secundary treatments were the ages of the birds (7, 14, 21, 28, 35 and 42 days). Statistical analyses confirmed no interactions among feeding program × temperature and feeding program × temperature × age on the broiler performance. Independently of the feeding program, the temperature of raising affected final weight, weight gain, feed intake and feed:gain ratio. Feeding program affected broiler final weight and weigth gain. Feeding program × age and temperature × age interactions affected the weights of the body at slaughter and the right leg muscle. These interactions were not significant for left leg muscle weight, cross-sectional right leg muscle area and right leg muscle weight:body weigth ratio. In conclusion, the environmental temperature affected the performance of broiler, but not the number, frequency and size of the myofibers in the flexor hallucis muscle. Early feed restriction can be utilized as management tool without changing the performance at slaughter age and the fiber composition of flexor hallucis longus muscle of male broilers.
Effect of Environmental Temperature and Feed Restriction on the Performance and Composition of the Skeletal Muscle Fibers in Broilers
Keywords: Broiler; Feed restriction; Fiber; Skeletal muscle; Temperature